Addition of sodium alginate and pectin to a carbohydrate-electrolyte solution does not influence substrate oxidation, gastrointestinal comfort, or cycling performance - Mears, S. A.; Worley, J.; Mason, G. S.; Hulston, C. J.; James, L. J. (Applied Physiology, Nutrition, and Metabolism, 2020)
Eight well-trained cyclists ingested 68 g/h of a carbohydrate-electrolyte solution with sodium alginate and pectin (CHO-ALG) or a taste and carbohydrate type-matched carbohydrate-electrolyte solution (CHO) during 120 min of cycling at 55% maximal power followed by an ~20 min time trial. Oxygen uptake, carbon dioxide production, blood glucose concentration, substrate oxidation, gastrointestinal symptoms, and time trial performance (CHO-ALG: 1219 ± 84 s, CHO: 1267 ± 102 s; P = 0.185) were not different between trials.